A checklist of the amphibians and reptiles of Honduras, with additions, comments on taxonomy, some recent taxonomic decisions, and areas of further studies needed - Mccranie, James R. (Zootaxa, 2015)
An updated checklist of the amphibians and reptiles of Honduras is provided. The list includes three amphibian species (Ptychohyla euthysanota, Bolitoglossa odonnelli, Oedipina chortiorum) and two reptile species (Laemanctus waltersi [elevated from subspecies status], Epictia phenops) not included in the most recent checklist of the amphibians and reptiles of the country. Also, one amphibian genus and species (Triprion petasatus) is removed from the country list and one Honduran lizard (Ctenosaura praeocularis) is synonymized with an older name. Comments where more study is needed are also included where pertinent. Authors, dates, and original spellings of the higher-level taxonomy of all taxa covered herein are also given. A total of 401 species (137 amphibians and 264 reptiles) are now known from the country with 111 species (27.7%) being Honduran endemics (52 amphibians and 59 reptiles).